Green skills for green industry: a review of literature - Chee, Sern Lai; Zaime, Adib Farhan; Ming, Foong Lee (IOP Publishing, 2018)
Apart from technical and generic skills, employers start looking for manpower with green skills which are much needed for promoting sustainable development in social, economic as well as environment. This article aimed at finding out the major green skills demanded by the green industry based on the existing literature. In the present study, document analysis was employed. The published articles and technical reports related to green skills in various disciplines were identified from electronic databases that includes ScienceDirect, Google Scholar, ResearchGate, and Academia. The findings from literature review revealed that there are ten most common green skills demanded by various industrial sectors, namely, design skill, leadership skill, management skill, energy skill, city planning skill, landscaping skill, communication skill, waste management skill, procurement skill, and financial skill. The role and directions of skill training institutions should be aligned with the needs and wants of the industrial sectors. Therefore, it is imperative for the skill training institutions to revise and revamp their curriculum in order to produce graduates with green skills to cater for the demand of manpower market.